Pengaruh Peran Kepala Sekolah dan Iklim Organisasi terhadap Komitmen Organisasi pada Guru Madrasah Aliyah Swasta - Satriawati, Mandira; Miyono, Noor; Wuryandini, Endang (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Organizational commitment is a condition and a person's sense of trust in the values of the organization as well as loyalty to the organization to work and having a strong desire to stay in the organization in order to realize the organization's goals. The aims of this research are (1) to determine the influence of the role of the principal on organizational commitment (2) to determine the influence of organizational climate on organizational commitment (3) to determine the influence of the role of the principal and organizational climate together on the organizational commitment of teachers at the Private Madrasah Aliyah, Pekalongan Regency. The population of this study were teachers at 6 private Madrasah Aliyah in Pekalongan Regency, totaling 117 people. The research sample was 91 teachers selected using proportional random sampling at each school. Validity, reliability and regression requirements tests, single regression and multiple regression tests using the SPSS for Windows version 23 program. The findings of the research results (1) the role of the principal has a significant influence on teachers' organizational commitment, the remaining 19.6% is influenced by other variables, (2) organizational climate has a significant influence on teachers' organizational commitment, the remaining 28.2% is influenced by other variables, (3) the role the principal and organizational climate together have a significant effect on teacher organizational commitment by 28.7%, Suggestions and recommendations (1) Ministry of Religion service supervisors increase supervision training for heads of Aliyah Madrasah. (2) School principals are more intensive in hiring teacher performance assessors so that teacher responsibility increases.